THE PROBLEM OF TRADITIONAL FELT AND CARPRET WEAVING AMONG KAZAKH WOMEN (19 - EARLY 20TH CENTURIES) (Journal of history, 2026)
Drawing on specialized scholarly literature, this article examines the traditional women’s household crafts of the Kazakhs during the 19th – early 20th centuries, with a particular focus on felt and carpet production. These crafts represent a historical formed system of women’s activities, characterised by a stable internal structure, established technologies and tools, effective mechanisms for the intergenerational transmission of knowledge and skills, and remarkable capacity to adapt to changing socio- culture conditions. Despite significant historical, natural, climatic, and environmental challenges, as well as periods of institutional pressure and the loss of  practices throughout the 20th century, both craft have retained their cultural relevance to the present day.The article demonstrates  that contemporary examples frequently diverge from their historical prototypes: the function of products, artistic canons, sources of  raw materials, and technological methods have all undergone change, resulting in partial loss of authenticity and functionality. In this context, the systematic scholarly study of traditional wool products, their typologies, and the finest historical examples from the 19th to early 20th century is of particular importance for historical and ethnological research.
Keywords: traditions, Kazakhs, women’s household crafts, felt and carpet products.